2018
DOI: 10.1002/hep.29715
|View full text |Cite
|
Sign up to set email alerts
|

Significance and mechanism of androgen receptor overexpression and androgen receptor/mechanistic target of rapamycin cross‐talk in hepatocellular carcinoma

Abstract: Nuclear AR overexpression is associated with the progression and prognosis of HCC. However, enzalutamide alone has limited therapeutic utility attributed to feedback activation of the AKT-mTOR pathway. Moreover, mTOR drives nuclear AR overexpression. Cotargeting AR and mTOR is a promising therapeutic strategy for HCC. (Hepatology 2018;67:2271-2286).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 46 publications
4
92
1
Order By: Relevance
“…International Publisher Furthermore, both higher serum androgen concentrations and the presence of AR gene variants containing shorter CAG repeats (leading to higher AR activity) have been linked to increased risk of hepatocarcinogenesis, especially of HBV-mediated HCC [7,10]. In addition, androgen/AR signals promote cancer cell stemness through direct activation of Nanog homeobox (NANOG) transcription in HCC [10].…”
Section: Ivyspringmentioning
confidence: 99%
See 1 more Smart Citation
“…International Publisher Furthermore, both higher serum androgen concentrations and the presence of AR gene variants containing shorter CAG repeats (leading to higher AR activity) have been linked to increased risk of hepatocarcinogenesis, especially of HBV-mediated HCC [7,10]. In addition, androgen/AR signals promote cancer cell stemness through direct activation of Nanog homeobox (NANOG) transcription in HCC [10].…”
Section: Ivyspringmentioning
confidence: 99%
“…The androgen receptor (AR) is a member of the nuclear steroid receptor superfamily [6,7], and is a transcription factor activated by ligand-dependent and ligand-independent mechanisms [8]. In response to stimulation by androgens, AR translocates into the nucleus, where it binds to androgen response elements (AREs), and regulates expression of genes related to cell growth and survival; it is in this role that AR serves an important regulator of pathogenesis in hepatocarcinogenesis [4].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, sex hormones and their receptors including AR showed influence on lung cancer in a mouse model, and AR expression together with Ki67 expression are associated with the survival outcome of non‐small‐cell lung cancer . As for liver cancer, AR is overexpressed in about 37% of hepatocellular carcinoma tumors, and AR overexpression stimulates oncogenic growth . In addition, it is reported that androgen promotes the growth of hepatocellular cancer cells by upregulating the transcription factor activity of ETS‐1 .…”
Section: Ar and Other Cancersmentioning
confidence: 99%
“…149 As for liver cancer, AR is overexpressed in about 37% of hepatocellular carcinoma tumors, and AR overexpression stimulates oncogenic growth. 150 In addition, it is reported that androgen promotes the growth of hepatocellular cancer cells by upregulating the transcription factor activity of ETS-1. 151 Presently, enzalutamide is being studied at phase I/II clinical trial for advanced hepatocellular carcinoma (NCT02528643 and NCT02642913).…”
Section: Ar and Bladder Cancer Kidney Cancer Lung Cancer And LIVmentioning
confidence: 99%
“…The animal protocol was approved by the Animal Ethics Committee of Sun Yat-Sen University Cancer Center. Subcutaneous xenograft models were established, and drug treatments were carried out as previously described (21)(22)(23)(24)(25). Four-week-old female BALB/c nude mice were used in this study.…”
Section: In Vivo Studies and Ihcmentioning
confidence: 99%